Human herpesvirus type 8 in tuberculosis patients with effusion. Issue 1 (December 2015) - Tsao, Shih-Ming; Lai, Chun-Liang; Lin, Ming-Nan; Tsai, Jen-Pi; Su, Cheng-Chuan
Abstract Background Many patients with tuberculosis (TB) are seropositive for human herpesvirus type 8 (HHV-8), and many patients with primary effusion lymphoma have high levels of HHV-8 DNA in their effusions. However, the status of HHV-8 in the effusions of patients with TB remains unclear. Methods Blood samples were collected from 129 patients with pulmonary TB and 129 age- and sex-matched healthy controls. Forty of the TB patients had pleural or peritoneal effusions, and 38 of these effusions were available. Both blood and effusion samples were analyzed for lymphocyte and monocyte counts and/or HHV-8 antibodies and DNA. Results TB patients with or without effusions had significantly greater HHV-8 seropositivity (p = 0.009) and titers of HHV-8 antibodies (p = 0.005) than healthy controls. The seropositivity and blood titers of HHV-8 antibodies were similar in TB patients with and without effusions. Among TB patients with effusions, similar percentages had seropositive plasma and seropositive effusions. Plasma samples of 6 TB patients, but none of the healthy controls, were positive for HHV-8 DNA (p = 0.03). TB patients with or without effusions had lower blood lymphocyte counts and higher blood monocyte counts than healthy controls (p < 0.0001 for both). TB patients with effusions had significantly lower blood lymphocyte counts than those without effusions (p = 0.035). Conclusions HHV-8 had similar seroprevalence in TB patients with and without effusions. However, TB patients with effusions had lower blood lymphocyte counts than those without effusions.